Some Improvements in a Gas Turbine Stator-Rotor Systems Core-Swirl Ratio Correlation - R. Da Soghe; B. Facchini; L. Innocenti; M. Micio (International Journal of Rotating Machinery)
The present work concerns the turbulent flow inside a rotor-stator cavity with superimposed throughflow. The authors focused their analysis on a simple two-faced disk cavity, without shrouds, with interdisk-spacing sufficiently large so that the boundary layers developed on each disk are separated and the flow is turbulent. In such a system, the solid body rotation of the core predicted by Batchelor can develop. The evolution of the core-swirl ratio of the rotating fluid with an outward throughflow is studied by applying a classical experimental correlation, inserted in a one-dimensional (1D) in-house developed code. Results are compared to those predicted by CFD computations. Due to the discrepancies revealed, the authors provided a correction of the experimental correlation, based on CFD computation. Results thus obtained are finally in good agreement with CFD predictions.